Anti‐tumor activity of CpG‐ODN aerosol in mouse lung metastases. Issue 2 (12th February 2013) - Sfondrini, Lucia; Sommariva, Michele; Tortoreto, Monica; Meini, Alessandra; Piconese, Silvia; Calvaruso, Marco; Van Rooijen, Nick; Bonecchi, Raffaella; Zaffaroni, Nadia; Colombo, Mario P.; Tagliabue, Elda; Balsari, Andrea
<x xml:space="preserve">Abstract</x> Studies in preclinical models have demonstrated the superior anti‐tumor effect of CpG oligodeoxynucleotides (CpG‐ODN) when administered at the tumor site rather than systemically. We evaluated the effect of aerosolized CpG‐ODN on lung metastases in mice injected with immunogenic N202.1A mammary carcinoma cells or weakly immunogenic B16 melanoma cells. Upon reaching the bronchoalveolar space, aerosolized CpG‐ODN activated a local immune response, as indicated by production of IL‐12p40, IFN‐γ and IL‐1β and by recruitment and maturation of DC cells in bronchoalveolar lavage fluid of mice. Treatment with aerosolized CpG‐ODN induced an expansion of CD4+ cells in lung and was more efficacious than systemic i.p. administration against experimental lung metastases of immunogenic N202.1A mammary carcinoma cells, whereas only i.p. delivery of CpG‐ODN provided anti‐tumor activity, which correlated with NK cell expansion in the lung, against lung metastases of the poorly immunogenic B16 melanoma. The inefficacy of aerosol therapy to induce NK expansion was related to the presence of immunosuppressive macrophages in B16 tumor‐bearing lungs, as mice depleted of these cells by clodronate treatment responded to aerosol CpG‐ODN through expansion of the NK cell population and significantly reduced numbers of lung metastases. Our results indicate that tumor immunogenicity and the tumor‐induced immunosuppressive environment are critical factors to the success of CpG therapy in the lung, and point to the value of routine sampling of the lung immune environment in defining an optimal immunotherapeutic strategy.